Structure–property relationship in epoxy‐silica hybrid nanocomposites: The role of organic solvent in achieving silica domains. Issue 4 (23rd July 2014) - Bakhshandeh, E.; Sobhani, S.; Jannesari, A.; Pakdel, A.S.; Sari, M.G.; Saeb, M.R.
Abstract : The thermo‐mechanical properties of a series of epoxy‐silica hybrid composites prepared through sol–gel process are evaluated in a manner that the effect of organic solvent on the formation of silica domains is highlighted. By means of infrared spectroscopy, small‐angle X‐ray scattering, scanning electron microscope, dynamic mechanical thermal analysis, and thermo‐gravimetric analyzer, the specimens were morphologically studied varying the type of organic solvent. Among polar and nonpolar solvents incorporated by the organic–inorganic hybrid system, a mixture of xylene and ethanol (3:1) was properly comparable with tetrahydrofuran (THF) solvent regarding appearance and thermo‐mechanical characteristics. Enhanced thermal stability and modulus was observed upon increasing solvent content. Also, a proper dispersion of silica domains throughout the epoxy was seen in the case that the xylene/ethanol mixture or THF served as solvent. It is to be emphasized that the assigned mixture is environmentally better than that of THF. J. VINYL ADDIT. TECHNOL., 21:305–313, 2015. © 2014 Society of Plastics Engineers